Perlindungan Hukum terhadap Hak Cipta di Era Digital Menurut Undang-Undang Nomor 28 Tahun 2014 - Wandi Arwana; Adnan; Gufran (Jurnal Hukum Lex Generalis, 2025)
The rise of digital technology presents new challenges in the legal protection of copyright as part of intellectual property rights. This study analyzes the effectiveness of Law Number 28 of 2014 on Copyright in addressing digital era infringements. The findings reveal that although the law explicitly regulates digital protection, its implementation faces technical and enforcement barriers. It concludes that strengthening derivative regulations and institutional synergy is essential to achieve copyright protection that adapts to technological advancement.